EFEKTIVITAS PEMBELAJARAN DEFERENSIASI DALAM MENGOPTIMALKAN HASIL BELAJAR SISWA - Hasanah, Siti Nur; Rahmawati, Dini; Handayani, Arri (Jurnal Visi Ilmu Pendidikan, 2026)
In the world of education, the main challenge faced by teachers is the diversity of student characteristics in one class. Differentiated learning strategies offer significant potential to increase learning effectiveness for students at various levels. The aim of this research is to evaluate the effectiveness of differentiated learning so that students can achieve optimal learning outcomes. Identifying the advantages and effective implementation methods for implementing differentiated learning at various levels of education is the main focus of this research. This article was written using a qualitative approach to literature review, which includes critical analysis of relevant articles. Ten articles published within the last five years"”from 2020 to 2024"”are the subject of this literature review. The results of the literature review show that differentiated learning can significantly increase student engagement and motivation, as well as their learning outcomes. This research found that differentiated learning is very effective in improving student learning outcomes. Thus, teachers are expected to be able to adopt this strategy in daily learning practice to improve student learning outcomes at various levels.Keywords: differentiated instruction, literature review, student learning outcomes.